International Handbook of Information Technology in Primary and Secondary Education - Voogt, Joke; Knezet, Gerald (Springer, 2008)
Since the introduction of the computer into education in the 1960’s its potential for K-12 education has been widely recognized. The terminology used, at times confusing due to rapid technology change, has continuously evolved.One ...
Keywords: TICE; numérique